The impact of project managers' transformational leadership on work crafting: explaining a moderating role of environmental dynamism in software project teams. (3rd November 2021) - Ahsan, Qurratulain; Abdullah, Muhammad Ibrahim; Chughtai, Muhammad Ahsan; Hafeez, Hira
This research aims to inspect whether project team behavioural integration and environmental dynamism explain the relationship between project managers' transformational leadership and project team members' work crafting. The author hypothesised that the team members would be expected to participate in work crafting in presence of transformational leaders when the project teams are behaviourally integrated and facing a dynamic environment. A self-administered questionnaire was used to explore the relationship between heterogeneous software project teams (N = 438). Results indicate a positive impact of transformational leaders to facilitate work crafting in project teams with team behavioural integration as a good mediator to strengthen this relationship and observed that high environmental dynamism leads to team integration and facilitate work crafting. The relationships explained are first of its nature to be tested on the software project teams in Pakistan. The study will recuperate the understanding of project-based organisations on improved work crafting of team members.